Measurement of safety social norms at organizations: Construct validation of a safety social norms survey - Fugas, C. S.; Silva, S. A.; Meliá, J. L. (Advances in Safety, Reliability and Risk Management. Proceedings of the European Safety and Reliability Conference, ESREL 2011, 2012)
This study was designed to test the reliability and construct validity of a questionnaire devoted to the measurement of social influences on safety at organizations in different sectors. The initial version of the Safety Social Norms Survey had 11 items four-scales that measured supervisors and coworkers' descriptive and injunctive safety norms. Respondents used a 7-point Likert-type frequency scale ranging from 1 (never) to 7 (always) to measure how often their supervisor and coworkers performed/think should be performed each safety behavior. This study was conducted in two different moments in time. The reliability and factorial validity of the instrument was assessed at Time 1 and the convergent and discriminant validity was assessed at Time 2. A sample of operational team workers from a Portuguese company (N = 250 at Time 1, and N = 353 at Time 2) participated voluntarily and anonymously in the study. The overall results of this study have demonstrated the reliability and construct validity of the proposed questionnaire, based on a correlated 4-Factor CFA model of Safety Social Norms.